Hematopoietic Stem/Progenitor Cells Directly Contribute to Arteriosclerotic Progression via Integrin β2. (24th March 2015) - Wang, Xuhong; Gao, Mingming; Schouteden, Sarah; Roebroek, Anton; Eggermont, Kristel; van Veldhoven, Paul P.; Liu, George; Peters, Thorsten; Scharffetter‐Kochanek, Karin; Verfaillie, Catherine M.; Feng, Yingmei
Abstract: Recent studies described the association between hematopoietic stem/progenitor cell (HSPC) expansion in the bone marrow (BM), leukocytosis in the peripheral blood, and accelerated atherosclerosis. We hypothesized that circulating HSPC may home to inflamed vessels, where they might contribute to inflammation and neointima formation. We demonstrated that Lin − Sca‐1 + cKit + (LSK cells) in BM and peripheral blood of LDLr −/− mice on high fat diet expressed significantly more integrin β2, which was responsible for LSK cell adhesion and migration toward ICAM‐1 in vitro, and homing to injured arteries in vivo, all of which were blocked with an anti‐CD18 blocking antibody. When homed LSK cells were isolated from ligated artery and injected to irradiated recipients, they resulted in BM reconstitution. Injection of CD18 +/+ LSK cells to immunodeficient Balb/C Rag2 − ɣC −/− recipients resulted in more severe inflammation and reinforced neointima formation in the ligated carotid artery, compared to mice injected with PBS and CD18 −/− LSK cells. Hypercholesterolemia stimulated ERK phosphorylation (pERK) in LSK cells of LDLr −/− mice in vivo. Blockade of pERK reduced ARF1 expression, leading to decreased integrin β2 function on HSPC. In addition, integrin β2 function could be regulated via ERK‐independent LRP1 pathway. Integrin β2 expression on HSPC is regulated by hypercholesterolemia, specifically LDL, in pERK‐dependent and ‐independent manners, leading to increased homing and localization of HSPC to injured arteries, which is highly correlated with arteriosclerosis. Stem Cells 2015;33:1230–1240